Multiwavelength generation by using a novel Brillouin-erbium fiber laser with double linear-cavity based on a double-pass Brillouin Pump (BP) amplification technique. (September 2019) - Ma, Lei; Zou, Hui; Xiong, Hui; Wu, Hui; Zhang, Yunshan
Highlights: A novel Brillouin fiber laser based on a double linear cavity has been proposed. 51 stable Stokes channels are generated with frequency spacing of 0.089 nm. The proposed laser structure achieves a low-threshold power of 39 mW. The OSNR of multiwavelength brillouin-erbium fiber lasers is more than 25 dB. Abstract: We propose and demonstrate an enhanced multiwavelength Brillouin-Erbium fiber laser by utilizing double linear cavity based on a double-pass pre-amplification technique. This simple structure is composed of two 24 km and 24.2 km single mode fiber (SMF) coils and two segments 13-m Erbium doped fibers (EDF). In order to obtain the Brillouin gain under low external injection Brillouin pump power, the BP is amplified in the linear cavity before entering into the SMF. In this experiment, so as to obtain the most Stokes lines, the optimization of 980 nm pump power and tunable laser source (TLS) power together with its corresponding wavelengths is very important. When setting the TLS power as 7.4 dBm and 980 nm pump power as 300 mW, a total of 51 Brillouin Stokes lines with frequency spacing of 0.089 nm are produced.